Amadeus [videorecording (DVD)] - Forman, Miloš; Abraham, F. Murray; Hulce, Tom, 1953-; Berridge, Elizabeth; Mozart, Wolfgang Amadeus, 1756-1791; Shaffer, Peter, 1926-2016 (Warner Home Video, 2002)
Adapted from Shaffer's play, the film presents the life of Antonio Salieri, a mediocre 18th century Viennese composer obsessed with and jealous of the musical genius of the age, Wolfgang Amadeus Mozart.